Labour immigration or slave trade in modernism : reflection of conditions, challenges and impacts on Cambodian female workers in country X - Hum Chan; Por Sovattha (2012)
This paper aims to define the status of Cambodian female workers in terms labour immigration or slave trade in modernism. Especially, the study identifies the employment conditions, challenges and impacts in country of destination X in South East Asia Region. Data was predominately descriptive nature extracted from documents and video interviews. A direct analysis was employed to discuss an issue. The results identified that Cambodian female workers migrated to work in country X under a legal immigration system, however, the workers were trafficked and exploited, forced to work overload, physically mistreated, sexually and emotionally abused by the employers. Consequently, they were psychically suffered and economically impacted caused aggravate poverty. Some workers died during working without appropriate legal actions. In conclusion, Cambodian female workers become victims of modern labour trade under a legal procedure. The finding from this study suggests further strengthening cooperation and intervention from countries of origin and destination is a mechanism to integrate regional economy.